Penyuluhan dengan Media Audiovisual Memengaruhi Tingkat Pengetahuan Ibu tentang Kebutuhan Dasar Ibu Hamil - Hadijah, Sitti; Hidayati, Hidayati; Indriani, Indriani; Amin, Wirawati (Jurnal Kebidanan Malakbi, 2021)
Efforts to accelerate the reduction of the Maternal Mortality Rate (MMR) can be carried out by ensuring that every mother is able to access quality maternal health services. Audiovisual media is one of the extension media that stimulates the senses of sight and hearing so as to increase mother's knowledge about the basic needs of pregnant women. This study aims to determine the effect of counseling with audiovisual media on the level of knowledge of mothers about the basic needs of pregnant women. The type of research used is a quasi-experimental research design non equivalent control group design. The sampling technique in this study used a consecutive sampling technique, as many as 32 respondents in the experimental group and 32 respondents in the control group. The statistical test used was the Wilcoxon test and the Mann Withney U-Test. From the results of the Wicoxon test in the two treatment groups, it was found that the p value (Asymp. Sig 2-tailed) was 0.000<0.05 so it could be concluded that there were significant differences in the extension group with audiovisual media and the extension group with leaflet media. The results of the analysis of the Mann Withney U-Test showed the largest p-value of 0.003<0.05 so it can be concluded that audiovisual counseling is more effectively used to increase mother's knowledge about the basic needs of pregnant women compared to leaflet media.